2006
DOI: 10.1111/j.1365-2958.2006.05227.x
|View full text |Cite
|
Sign up to set email alerts
|

Use of a marker plasmid to examine differential rates of growth and death between clinical and environmental strains of Vibrio vulnificus in experimentally infected mice

Abstract: SummaryVibrio vulnificus is Gram-negative bacterium that contaminates oysters, causing highly lethal sepsis after consumption of raw oysters and wound infection. We previously described two sets of V. vulnificus strains with different levels of virulence in subcutaneously inoculated iron dextran-treated mice. Both virulent, clinical strains and attenuated, environmental strains could be recovered in high numbers from skin lesions and livers; however, the attenuated environmental strains required significantly … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
17
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 38 publications
(56 reference statements)
2
17
0
Order By: Relevance
“…In a recent study, Adams et al (1) determined that parenteral iron inoculation in mice increases the iron content in the epidermis and dermis at a high iron dose (5 mg). We did not measure the iron concentration in the skin of the animals used in this study, but our results demonstrate that one of the components involved in the fast replication of V. vulnificus in that organ, previously observed by Starks et al (62,63), is the active transport of iron (which may be mainly from transferrin), as demonstrated by the involvement of the tonB genes, which is still crucial for a successful infection in this animal model. It is worth noticing that in iron-overloaded animals the wild-type strain can establish a rapid infection and that the LD 50 value is 4 to 5 log smaller than that for non-iron-treated animals.…”
Section: Discussionmentioning
confidence: 59%
See 1 more Smart Citation
“…In a recent study, Adams et al (1) determined that parenteral iron inoculation in mice increases the iron content in the epidermis and dermis at a high iron dose (5 mg). We did not measure the iron concentration in the skin of the animals used in this study, but our results demonstrate that one of the components involved in the fast replication of V. vulnificus in that organ, previously observed by Starks et al (62,63), is the active transport of iron (which may be mainly from transferrin), as demonstrated by the involvement of the tonB genes, which is still crucial for a successful infection in this animal model. It is worth noticing that in iron-overloaded animals the wild-type strain can establish a rapid infection and that the LD 50 value is 4 to 5 log smaller than that for non-iron-treated animals.…”
Section: Discussionmentioning
confidence: 59%
“…Thus, the lethal concentration of bacteria can be reached faster in the iron-overloaded mouse model (19). Starks et al (62) showed that iron increased the replication of V. vulnificus in skin, but they also observed a reduction in susceptibility of some strains to being killed by animal defenses. There is also a correlation between utilization of iron from transferrin and virulence, in which the siderophore vulnibactin appears to play a role in infections in suckling mice (34,70) and in normal mice (23), where transferrin saturation levels are expected to be close to the normal range.…”
mentioning
confidence: 99%
“…To analyze the mode of action of minihepcidin PR73, we used V. vulnificus CMCP6 containing pGTR905, a marker plasmid that confers resistance to chloramphenicol, as described in Starks et al (Starks et al, 2006). The plasmid replicates only in the presence of arabinose, which is not found in mouse tissues.…”
Section: Methodsmentioning
confidence: 99%
“…Blood taken from patients with chronic liver disease showed decreased neutrophil activity compared to the blood of healthy individuals, and survival of V. vulnificus in human blood is inversely correlated with phagocytosis by neutrophils (44). Based on these data and a study showing increased neutrophil concentrations in the peritoneal cavity upon infection with V. vulnificus, the response of neutrophils to V. vulnificus has been implicated as a disease determinant for this organism (44,56,144,154). One of these studies, however, did use unencapsulated strains (the significance of which is discussed later in this review), thus diminishing the potential role neutrophils play in controlling V. vulnificus infection (44,154).…”
Section: Host Resistancementioning
confidence: 99%
“…Precisely how excess serum iron confers an advantage to V. vulnificus is still unclear; however, two theories have been put forth. One study evaluating growth of this bacterium in mice demonstrated that the presence of excess iron dramatically increased the growth rates of clinical strains, suggesting that excess iron enhances growth of this pathogen (144). Other researchers have found that excess iron resulted in decreased neutrophil activity and concluded that excess iron resulted in a compromised immune response (45).…”
Section: Iron Acquisitionmentioning
confidence: 99%